2020
DOI: 10.1038/s41598-020-69781-7
|View full text |Cite
|
Sign up to set email alerts
|

Physical and mechanical properties of wood and their geographic variations in Larix sibirica trees naturally grown in Mongolia

Abstract: We examined the physical and mechanical properties of wood in Siberian larch (Larix sibirica) trees that grow naturally in five Mongolian provenances (Khentii, Arkhangai, Zavkhan, Khuvsgul, and Selenge) and the geographic variations between them. Five trees with stem diameters of 20 to 30 cm at 1.3 m above ground were collected from each provenance. The mean values of the modulus of elasticity (MOE), modulus of rupture (MOR), compressive strength parallel to grain (CS), and shearing strength (SS) ranged from 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 36 publications
(66 reference statements)
2
5
0
Order By: Relevance
“…Thus, further research is necessary to elucidate the relationships between microfibril angle and the mechanical properties of juvenile wood in P. sylvestris. On the other hand, correlation coefficients between mechanical properties were reported by several researchers (Pikk and Kask 2004, Tumenjargal et al 2020, Sarkhad et al 2022. Similar results were also obtained in the present study, suggesting that mechanical properties can be evaluated by other mechanical properties.…”
Section: Resultssupporting
confidence: 92%
“…Thus, further research is necessary to elucidate the relationships between microfibril angle and the mechanical properties of juvenile wood in P. sylvestris. On the other hand, correlation coefficients between mechanical properties were reported by several researchers (Pikk and Kask 2004, Tumenjargal et al 2020, Sarkhad et al 2022. Similar results were also obtained in the present study, suggesting that mechanical properties can be evaluated by other mechanical properties.…”
Section: Resultssupporting
confidence: 92%
“…The results showed that the boundary between juvenile and mature wood for each tree ranged between the 19th and 25th annual rings from the pith (Table 5). The boundary age obtained in the present study was similar to that of previous studies on other species [31][32][33]. Although the estimated boundary varies due to species, age, or methods, a nonlinear mixed-effects model based on the Michaelis-Menten equation is an alternative tool for determining the boundary between juvenile and mature wood with various random effects, such as environmental and genetic factors.…”
Section: Wood Propertiessupporting
confidence: 85%
“…As shown in Table 4 In softwood species, wood properties differ dramatically between juvenile and mature wood [4,26,28,31]. Tracheid length has been used as a trait to determine the boundary between juvenile wood and mature wood [31][32][33]. Shiokura [32] used a logarithmic formula to describe the radial variation of tracheid length, and he also pointed out that for distinguishing between juvenile and mature wood, 1% of the increasing rate for tracheid length was desirable.…”
Section: Wood Propertiesmentioning
confidence: 99%
“…Although statistical analysis has been used for processing complex data in wood science, the classification of wood species with respect to their physiomechanical properties is rare. The reason is twofold: 1) There are many physiomechanical properties, and these properties have certain variations among and within wood species [30]; 2) The recognition accuracy is low when extracting information from the properties [31]. Rational classification based on the physiomechanical properties is helpful for exploring the "properties-applications" relationships of wood and its rational utilizations.…”
Section: Introductionmentioning
confidence: 99%